HR Audit-Based SOP Development for Sustainable Workforce Retention in Culinary MSMEs Kedai Bakso Pemuda Spesial Kuah Bening - Mega Fianita Fadilah; Hanif Rani Iswari; Sudiyono Sudiyono; Muhammad Yusuf Bahtiar; Viony Alfiyatu Zahroh; Ayu Wandani Mustika Rahma Ba'its Nur (Trescode Green Organization, 2025)
This community service project was conducted to address the high turnover rate among mobile bakso sales employees at Kedai Bakso Pemuda Spesial Kuah Bening in Malang City. The initiative aimed to enhance workforce stability through a structured Human Resource Audit (HRA) and the development of Standard Operating Procedures (SOPs) based on job analysis and placement principles. The project applied a participatory action approach, involving both management and employees in diagnosing human resource problems and co-developing solutions. The HRA process included five key stages: problem identification, job analysis, job evaluation, job placement, and SOP formulation, followed by monitoring and review. Data were collected through structured interviews, observations, and performance record analysis. Findings revealed that unclear job boundaries, overlapping responsibilities, and a lack of standardized performance monitoring were the primary causes of employee dissatisfaction and turnover. As a result, four major SOPs were developed covering recruitment and orientation, route management, sales operation, and reporting procedures. These SOPs provided clear task guidelines, transparent performance metrics, and fair compensation mechanisms. Within two months of implementation, employee turnover decreased by 25%, and satisfaction levels improved significantly, especially regarding communication and role clarity. This program demonstrates that human resource auditing, when combined with participatory SOP design, can transform informal MSME labor structures into efficient and sustainable systems. The model offers a replicable framework for other small enterprises that rely on mobile or field-based sales personnel, promoting workforce professionalism and long-term business resilience.